Technical Innovation, solving the Data Spaces and Marketplaces Interoperability Problems for the Global Data-Driven Economy: i3-MARKET Series - Part III: The i3-MARKET FOSS Handbook - Serrano, Martín; Zappa, Achille; Ashraf, Waheed; Friess, Edgar; Martinez, Iván; Mateus, Márcio; Maló, Pedro; Amicone, Alessandro; Bieliauskaite, Justina; Cugurra, Marina (River Publishers Series in Computing and Information Science and Technology, 2024)
In the third i3-MARKET series book we focus on the best practices and simplest software methods and mechanisms that allow the i3-MARKET backplane reference implementation to be instantiated, tested and validated even before the technical expert and developer communities decide to integrate the i3-MARKET as a reference implementation or adopted open-source software tools. The purpose of this book is to offer a clear understanding of the technological components as well as the software infrastructures, and the steps to be followed to avoid overwhelming the deployment activity. i3-MARKET has three industrial pilots defined in terms of data resources used to deploy data-driven applications that use the most of the i3-MARKET backplane services and functionalities. The different software technologies developed, including the use of open-source frameworks, within the context of the i3-MARKET is considered as a bill of software artefacts of the resources needed to perform demonstrators, proof of concepts, and prototype solutions. The i3-MARKET handbook can be used as input for configurators and developers to set up and pre-test testbeds and therefore it is extremely valuable to organizations if used properly.